Peran Media Penyiaran Dalam Proses Pemulihan Pasca Bencana - Fitri Murfiani (Institut Seni Indonesia Surakarta, 2006)
Broadcasting media is very important for human life alteration. Radio and television are broadcasting medias which are efisien to reach large audiences. Media has a big attention for disaster, such as earthquake that happened in Yogyakarta. Disaster usually creates uncertain situation. It is also as a big news to be broadcasted by the media. Media must have a control function for the government and social institutions. National television is also limited in spreading/broadcasting informations in a long duration because the television must give an up to date information or we call it a hot news. That is why local media must take more roles in this recovering process.Keyword: Media, Penyiaran, Pasca Bencana.